The revolution of the anti-diabetic drugs in cardiology. (29th March 2020) - Verdecchia, Paolo; Angeli, Fabio; Cavallini, Claudio; Aita, Adolfo; Turturiello, Dario; Reboldi, Gianpaolo
Abstract: Beginning in December 2008, under the auspices of Food and Drug Administration, numerous controlled clinical trial were planned, and in part completed, concerning the cardiovascular (CV) effects of hypoglycaemic drug in patients with Type 2 diabetes mellitus. At least 9 studies have been concluded, 13 are still open, and 4 have been initiated and closed ahead of time. Of the nine completed studies, three concerned inhibitor of the dipeptidyl peptidase 4 (inhibitors of DPP-4), four the glucagon-like peptide 1 agonist (GLP-1 agonist), and two the inhibitor of sodium-glucose co-transporter-2 (inhibitors of SGLT-2). Only four studies demonstrated the superiority, and not the mere 'non-inferiority', of the anti-diabetic drugs compared to placebo, in addition to standard treatment, in terms of reduction of the primary endpoint (CV death, non-fatal myocardial infarction, and non-fatal stroke). Two of the four studies regarded GLP-1 analogues (liraglutide and semaglutide), and two inhibitors of SGLT-2 (empaglifozin and canaglifozin). As a whole, these studies provided solid data supporting major beneficial CV effects of anti-diabetic drugs. During the next 3–4 years, an equal number of studies will be completed and published, so we will soon have the 'final word' on this issue. In the meantime, the clinical cardiologist should become familiar with these drugs, selecting the patients able to gain the best clinical advantage from this treatment, also by establishing a close relationship with the diabetologist.